PENGARUH BIOURINE SAPI TERHADAP PERTUMBUHAN BIBIT KARET (Hevea brasiliensis Mull. Arg) ASAL STUM MATA TIDUR (The Effect of Cattle Biourine to The Growth of Rubber Seedling from Stum Rubber) - Nyimas Myrna E. Fathia; Helmi Salim; Zul Fahri Gani (Bioplantae, 2013)
The objective of this research was to determine the best biourine concentration on the rubber seedling. This research was conducted at Teaching and Research Farm, Agriculture Faculty, Mendalo Darat, Jambi. This experiment was designed using completely Randomized Design with five treatment, and three replications. The treatments were the level of biourine concentration : uo= 0% bio-urine, u1= 2,5%, u2= 5,0%, u3= 7,5% dan u4= 10,0%. Three were 15 units of treatments. Statical analysis showed that cattle biourine at 7, 5 % gave the best growth of rubber seedling, shoot height and root dry weight. Key word: Urine , rubber, shoot